Pathogenic Triad in Bacterial Meningitis: Pathogen Invasion, NF-κB Activation, and Leukocyte Transmigration that Occur at the Blood-Brain Barrier - Wang, Shifu; Peng, Liang; Gai, Zhongtao; Zhang, Lehai; Jong, Ambrose; Cao, Hong; Huang, Sheng-He (Frontiers in Microbiology, 2016)
Bacterial meningitis remains the leading cause of disabilities worldwide. This life-threatening disease has a high mortality rate despite the availability of antibiotics and improved critical care. The interactions between bacterial surface components and host defense systems that initiate bacterial meningitis have been studied in molecular and cellular detail over the past several decades. Bacterial meningitis commonly exhibits triad hallmark features (THFs): pathogen penetration, nuclear factor-kappaB (NF-B) activation in coordination with type 1 interferon (IFN) signaling and leukocyte transmigration that occur at the blood-brain barrier (BBB), which consists mainly of brain microvascular endothelial cells (BMEC). This review outlines the progression of these early inter-correlated events contributing to the central nervous system (CNS) inflammation and injury during the pathogenesis of bacterial meningitis. A better understanding of these issues is not only imperative to elucidating the pathogenic mechanism of bacterial meningitis, but may also provide the in-depth insight into the development of novel therapeutic interventions against this disease.